Distribution of serotypes and molecular characterization of avian pathogenic Escherichia coli isolated from chicken died of colibacillosis - T K RAJKHOWA; C VANLALRUATI; L HAUHNAR; K JAMOH (Indian Journal of Animal Sciences, 2021)
Avian pathogenic Escherichia coli (APEC), can inflicts not only severe losses to the poultry industry due to morbidity and condemnations but also can pose a serious public health and food biosafety concern by playing a key role as an acceptor and donor of transmissible antimicrobial resistance mechanisms. Our studies on 71 APEC strains isolated from chicken died of colibacillosis, in Mizoram, India, revealed 13 different serotypes with predominance of O83 (35.21%). Of the 71 serotyped APEC strains, 67 (94.37%) are characterized as multidrug resistant with antimicrobial resistance as high as against 16 antibiotics tested. These strains harboured combination of up to 8 antimicrobial resistance genes tetA (92.96%), intl (70.42%), sul1 (59.15%), sul2 (56.34%), Dfrla (53.52%), Aad A (50.70%) in more than 50% of the strains. In addition, 8 different virulence associated genes with combination up to 7 genes together and with maximum frequency of fimC (97.18%), hlyE (80.28%), tsh (61.97%), fyuA (60.56%), irp2 (59.15%) and iuCD (57.75%) were detected. This is the first report on prevalence and heterogeneity of serotypes, pattern of antibiotic resistance and virulence genes content among APEC strains from North East region of India.